Structure of reticulated python (Malayopython reticulatus) tongue using scanning electron microscopy and light microscopy - MARTINA MARINA; GOLDA RANI SARAGIH; ULAYATUL KUSTIATI; TEGUH BUDIPITOJO; HERY WIJAYANTO; TRI WAHYU PANGESTININGSIH; ARIANA ARIANA; WORO DANUR WENDO; VISTA BUDIARIATI; DWI LILIEK KUSINDARTA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Marina M, Saragih GR, Kustiati U, Budipitojo T, Wijayanto H, Pangestiningsih TW, Ariana, Wendo WD, Budiariati V, Kusindarta DL. 2024. Structure of reticulated python (Malayopython reticulatus) tongue using scanning electron microscopy and light microscopy. Biodiversitas 25: 1596-1604. Reticulated python (Malayopython reticulatus) is the longest snake in the world. It belongs to order Squamata, suborder Serpentes, family Pythonidae, and genus Malayopython. The size of this snake can reach up to 6-8 m, which makes it the largest member of Pythonidae family. The tongue of Malayopython reticulatus (Schneider, 1801) is unique in that it serves the chemosensory process by capturing and carrying airborne chemical particles to Jacobson's or vomeronasal organs, so it would be very interesting to know the morphology of the lingual papillae of the tongue of M. reticulatus. This research aimed to determine the morphological and histological structures of M. reticulatus tongue via Scanning Electron Microscopy (SEM) and Hematoxylin-Eosin (HE) staining. Macroscopically, the tongue was divided into the apex, corpus, and radix. This organ is elongated with bifurcation. The dorsal anterior part tends to be blackish, whereas the posterior part tends to be lighter to reddish in color. SEM observation showed that the reticulated python tongue has microfacets and micropores on the dorsal side but lack papillae and taste buds. Histological results (HE staining) revealed that the tongue is divided into a mucosal layer and a muscular layer. The mucosal layer consists of lamina epithelial mucosa and lamina propria mucosa. Melanin exists in the lamina propria mucosa. The muscular layer comprises longitudinal, transverse, and vertical muscles and also lack papillae and taste buds.